Pengaruh Promosi Dan Citra Sekolah Terhadap Keputusan Siswa Memilih Sekolah Pada Smks Islam Asy Syuhada Rumpin Bogor - Ahmad Arif; Ahmad Nurhadi (JURNAL RUMPUN MANAJEMEN DAN EKONOMI, 2026)
Abstract. This study aims to analyze the financial performance of PT Hanjaya Mandala Sampoerna Tbk for the period 2014–2024, as measured by liquidity, solvency, and profitability ratios. The research employs a quantitative method with a descriptive approach. The data used are secondary data obtained from the company’s annual financial reports published by the Indonesia Stock Exchange (IDX). The data analysis technique used in this study is financial ratio analysis, which includes the current ratio, quick ratio, cash ratio, debt to equity ratio, debt to asset ratio, long-term debt to equity ratio, return on assets, return on equity, and net profit margin. The results show that, in terms of liquidity, the current ratio is 322.02%, the quick ratio is 153.57%, and the cash ratio is 70.06%. Based on the Decree of the Minister of Finance No. 740/KMK.00/1989, these results indicate that the company’s liquidity condition is very healthy. In terms of solvency, the debt to equity ratio is 62.32%, the debt to asset ratio is 35.73%, and the long-term debt to equity ratio is 7.18%, all of which indicate an unhealthy condition, as the values are below 100%. Meanwhile, from the profitability perspective, the return on assets is 21.26%, the return on equity is 32.71%, and the net profit margin is 10.31%, showing that the company’s profitability level is very healthy. Keywords: Liquidity Ratio, Solvency Ratio, profitability ratio, Financial Performance